Ferric sodium pyrophosphate phosphate positive electrode material and preparation method thereof, and electrochemical device
Patent Information
- Application Number
- CN202511971651.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-12-24
AI Technical Summary
[0003]然而,NFPP正极材料的导电性能较差,导致NFPP正极材料的循环性能和倍率性能下降,阻碍了NFPP正极材料的产业化发展
1.包覆物料包括第二碳源和含有三嗪结构的化合物,可实现NFPP表面g-C3N4原位包覆,并形成较完整且连续的包覆层,能够有效提高包覆层的石墨化程度、导电性和稳定性,提供良好的导电网络,降低NFPP正极材料的电阻率,有效提高NFPP正极材料的循环性能和倍率性能,并拓宽NFPP正极材料适用的温度范围。
Smart Images

Figure CN121672460B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, specifically to a sodium iron pyrophosphate cathode material and its preparation method, as well as an electrochemical device. Background Technology
[0002] Sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7, NFPP) is used as a cathode material for sodium-ion batteries, possessing high theoretical specific capacity and three-dimensional Na+. + It features a transmission channel, good long-term cycling stability, and good low-temperature performance, and the NFPP exhibits minimal volume change during charge and discharge.
[0003] However, the poor conductivity of NFPP cathode materials leads to a decline in their cycle performance and rate capability, hindering the industrialization of NFPP cathode materials. Summary of the Invention
[0004] In view of this, in order to solve at least one of the above technical problems, this application provides a method for preparing sodium iron pyrophosphate cathode material.
[0005] In addition, embodiments of this application also provide a sodium iron pyrophosphate cathode material and an electrochemical device using the sodium iron pyrophosphate cathode material.
[0006] In a first aspect, embodiments of this application provide a method for preparing a sodium iron pyrophosphate cathode material. The method includes: mixing a sodium source, an iron source, a phosphorus source, and a first carbon source to obtain a first mixture, and sintering the first mixture once to obtain a sodium iron pyrophosphate precursor; and mixing the sodium iron pyrophosphate precursor with a coating material to obtain a second mixture, and sintering the second mixture a second time to obtain the sodium iron pyrophosphate cathode material with a coating layer, wherein the coating material includes a second carbon source and a compound containing a triazine structure.
[0007] Based on the first aspect, in some possible embodiments, the temperature of the secondary sintering is 450℃~600℃, and the holding time of the secondary sintering is 5h~10h.
[0008] Based on the first aspect, in some possible embodiments, the mass percentage of the coating material to the sodium iron pyrophosphate precursor is 7% to 9%.
[0009] Based on the first aspect, in some possible embodiments, the mass ratio of the second carbon source to the compound in the coating material is (1.3~8):1.
[0010] Based on the first aspect, in some possible embodiments, the mass percentage of the compound to the sodium iron pyrophosphate precursor is 1% to 3%; and / or the mass percentage of the second carbon source to the sodium iron pyrophosphate precursor is 4% to 8%.
[0011] Based on the first aspect, in some possible embodiments, the compound includes at least one of urea, melamine, dicyandiamide, and thiourea.
[0012] Based on the first aspect, in some possible embodiments, the second carbon source includes at least one of glucose, sucrose, starch, citric acid, and polyethylene glycol.
[0013] Based on the first aspect, in some possible embodiments, the second carbon source is glucose.
[0014] Secondly, this application provides a sodium iron pyrophosphate cathode material, which is prepared by the aforementioned method for preparing sodium iron pyrophosphate cathode materials. The sodium iron pyrophosphate cathode material includes a sodium iron pyrophosphate matrix and a coating layer located on the outer layer of the sodium iron pyrophosphate matrix, wherein the coating layer contains g-C3N4.
[0015] Thirdly, embodiments of this application also provide an electrochemical device, the electrochemical device including a positive electrode sheet, the positive electrode sheet including a positive electrode material, the positive electrode material being the aforementioned sodium iron pyrophosphate positive electrode material.
[0016] Compared to existing technologies, the method for preparing sodium iron pyrophosphate (NFPP) cathode material provided in this application embodiment, through secondary sintering of the NFPP precursor, enables the NFPP precursor to decompose and recombine to form NFPP, improving the phase purity and crystallinity of NFPP and thus enhancing its electrochemical performance. Simultaneously, during the secondary sintering process, a coating layer is formed on the surface of the NFPP by the coating material. The triazine-containing compound in the coating material reacts in situ on the outer layer of the NFPP to form g-C3N4. Due to the unique two-dimensional layered structure of g-C3N4, this coating layer exhibits high conductivity, good stability, and fewer high-temperature side reactions. g-C3N4 can also connect the amorphous carbon formed by the second carbon source, with both forming the coating layer together. This rapidly establishes electronic pathways and constructs a complete conductive network, thereby simply and efficiently improving the conductivity of the NFPP cathode material, resulting in excellent cycle performance and rate performance. Attached Figure Description
[0017] Figure 1 This is a process flow diagram of the preparation method of sodium iron pyrophosphate cathode material provided in an embodiment of this application.
[0018] Figure 2 This is a schematic flowchart illustrating a method for preparing sodium iron pyrophosphate cathode material according to an embodiment of this application.
[0019] Figure 3 This is a scanning electron microscope image of the sodium iron pyrophosphate cathode material provided in Example 1 of this application.
[0020] Figure 4 This is a scanning electron microscope image of the sodium iron pyrophosphate cathode material provided in Comparative Example 1 of this application.
[0021] Figure 5 This is a scanning electron microscope image of the sodium iron pyrophosphate cathode material provided in Example 7 of this application.
[0022] Figure 6 This is a scanning electron microscope image of the sodium iron pyrophosphate cathode material provided in Comparative Example 3 of this application.
[0023] Figure 7 This is a scanning electron microscope image of the sodium iron pyrophosphate cathode material provided in Comparative Example 4 of this application.
[0024] Figure 8 The X-ray diffraction patterns are those of the sodium iron pyrophosphate cathode materials provided in Example 1 and Comparative Example 4 of this application.
[0025] Figure 9 The 0.1C charge-discharge curves of batteries prepared using the sodium iron pyrophosphate cathode material provided in Examples 1, 7 and Comparative Example 1 of this application.
[0026] Figure 10 The 0.1C charge-discharge curves are for batteries prepared using the sodium iron pyrophosphate cathode material provided in Example 1 and Comparative Examples 3-4 of this application.
[0027] Figure 11 A high-temperature cycle capacity retention curve of a battery prepared using the sodium iron pyrophosphate cathode material provided in Example 1 of this application.
[0028] Figure 12 The 5C charge-discharge curve of the battery prepared using the sodium iron pyrophosphate cathode material provided in Example 1 of this application. Detailed Implementation
[0029] The embodiments of this application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; where there is no conflict, the implementation methods and features of the implementation methods of this application can be combined with each other; many specific details are set forth in the following description to provide a full understanding of this application, and the described implementation methods are only a part of the implementation methods of this application, and not all of the implementation methods.
[0030] The inventors of this application have discovered that the sintering temperature range during the preparation of sodium iron pyrophosphate (NFPP) cathode materials is relatively narrow. Phase formation typically begins around 400℃ and is completed around 500℃. Above 600℃, some decomposition may occur. The sintering process easily generates electrochemically inert sodium iron phosphate (NFP) impurities, leading to deterioration of material performance. Secondly, PO4 in NFPP... 3- The inherent isolation properties of the functional groups result in poor intrinsic electronic conductivity of NFPP, which adversely affects cycle and rate performance. Existing improvement measures usually involve carbon coating of NFPP substrate. However, the graphitization temperature of existing carbon sources (such as polyethylene glycol) does not match the sintering temperature of NFPP phase formation. The resulting carbon layer has a low degree of graphitization and poor conductivity, making it difficult to effectively modify NFPP cathode materials.
[0031] For this purpose, please refer to Figure 1 and Figure 2 As shown in the figure, this application provides a method for preparing sodium iron pyrophosphate cathode material, which specifically includes the following steps: Step S1: Sodium source, iron source, phosphorus source and first carbon source are mixed and ground to obtain first slurry, and the first slurry is spray dried and sintered once to obtain sodium iron pyrophosphate precursor.
[0032] In some embodiments, the sodium source, iron source, phosphorus source, and first carbon source can be mixed together or mixed sequentially. The sequential mixing order can be: first adding the soluble material, then adding the reactant combination (e.g., sodium carbonate and sodium dihydrogen phosphate), and finally adding the insoluble material that does not react at room temperature after the reaction. This improves the uniformity of the mixture.
[0033] In some embodiments, in step S1, the first mixture may be further ground to obtain a first slurry. Grinding helps to further improve the uniformity of the mixture and control the particle size in the first slurry within a suitable range. Specifically, a solvent (e.g., at least one of water and ethanol) may be added to the first mixture before grinding. Grinding in a solvent helps to improve grinding efficiency.
[0034] In some embodiments, the median particle size D50 of the first slurry is 0.8 μm to 1.2 μm, which is beneficial for controlling the particle size of the primary sintering material. The median particle size D50 of the first slurry can be, for example, 0.80 μm, 0.85 μm, 0.90 μm, 1.0 μm, 1.1 μm, 1.2 μm, or any value within the range of any two of the above values.
[0035] In some embodiments, the diameter of the grinding beads used in step S1 can be 0.6 mm to 1.0 mm.
[0036] Furthermore, before the first sintering, the first slurry can be spray-dried. Spray drying is beneficial for obtaining a dry first spray material with relatively uniform particle size and good flowability, which can improve the uniformity of the first sintering.
[0037] In some embodiments, in step S1, the inlet air temperature of the spray dryer can be 180°C to 240°C, preferably 230°C, and the outlet air temperature can be 75°C to 120°C, preferably 90°C, which is beneficial for fully removing solvents and other volatile impurities from the first slurry.
[0038] In some embodiments, the heating rate for primary sintering can be 2°C / min to 5°C / min. Slow heating is beneficial for improving the uniformity of the reaction of Na, Fe, and P elements, reducing local overheating or uneven reaction during primary sintering, and also for forming primary sintered material with uniform particle size and relatively stable structure. The heating rate for primary sintering can, exemplarily, be 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, or any value within the range of any two of the above values.
[0039] In some embodiments, the primary sintering temperature is 300℃~500℃. Such suitable sintering temperatures promote thorough and uniform mixing of elements and suppress the formation of the impurity phase NaFePO4 (sodium iron phosphate, NFP). The primary sintering temperature can, exemplarily, be 300℃, 350℃, 400℃, 450℃, 500℃, or any value within the range of any two of the above values. The holding time for the primary sintering is 5h~10h, which facilitates thorough mixing and sintering of the raw materials at a lower temperature. The holding time for the primary sintering can, exemplarily, be 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.
[0040] In some embodiments, the molar ratio of elements in the sodium, iron, and phosphorus sources, Na:Fe:P, is 4:(2.8~3.2):4, which is beneficial to improving the phase purity of the final NFPP and reducing the formation of the inactive sodium iron phosphate (NFP) impurity phase. The molar ratio Na:Fe:P can exemplary be 4:2.8:4, 4:2.9:4, 4:3.0:4, 4:3.1:4, 4:3.2:4, or any value within the range of any two of the above values.
[0041] In some embodiments, the first carbon source accounts for 6% to 10% of the iron source by mass, which is beneficial for the first carbon source to fully disperse the raw materials such as sodium, iron, and phosphorus sources and to provide sufficient reducibility. This mass percentage can be exemplarily 6%, 7%, 8%, 9%, 10%, or any value within the range of any two of the above values.
[0042] In some embodiments, the first carbon source may include at least one of glucose, sucrose, starch, citric acid, and polyethylene glycol.
[0043] In a single sintering process, the primary carbon source can act as a reducing agent, helping to regulate the oxidation state of iron and reduce Fe during the sintering process. 2+ Oxidized to Fe 3+ This reduces the formation of the inactive sodium iron phosphate (NFP) impurity phase, thereby maintaining the ideal stoichiometry and electrochemical activity of the material.
[0044] In some embodiments, the first mixture may also contain additives, which may include titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide, or niobium pentoxide, which are beneficial to improving the structural stability and conductivity of the NFPP cathode material.
[0045] Furthermore, the metal element in the additive accounts for 0.15%~0.45% of the NFPP mass in the theoretically calculated NFPP cathode material, which is beneficial for the effective modification of NFPP by the metal element in the additive. The theoretical calculation method for the NFPP mass is to calculate the theoretical molar amount of NFPP based on the NFPP molecular formula (Na4Fe3(PO4)2P2O7) and the molar amounts of the main elements (Na, Fe, and P) in the specific raw materials, and then calculate the theoretical mass.
[0046] In some embodiments, the sodium source may include at least one of sodium carbonate, sodium hydroxide, sodium oxalate, sodium citrate, monosodium glutamate, sodium dihydrogen phosphate, sodium dihydrogen phosphate hydrate, disodium hydrogen phosphate, disodium hydrogen phosphate hydrate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0047] In some embodiments, the iron source may include at least one of iron phosphate, iron oxide, iron tetroxide, iron hydroxide, and ferrous oxalate dihydrate.
[0048] In some embodiments, the phosphorus source may include at least one of iron phosphate, phosphoric acid, sodium dihydrogen phosphate, sodium dihydrogen phosphate hydrate, disodium hydrogen phosphate, disodium hydrogen phosphate hydrate, sodium pyrophosphate, disodium dihydrogen pyrophosphate, monoammonium phosphate, and ammonium dihydrogen phosphate.
[0049] In some embodiments, the carbon content of the NFPP precursor can be 0.5% to 0.7%, which is beneficial for reducing ferric iron in the raw material to ferrous iron while simultaneously crystallizing and forming a preliminary carbon layer, thus reducing the formation of impurity phases such as iron phosphide. The carbon content of the NFPP precursor can, exemplarily, be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, or any value within the range of any two of the above values.
[0050] Step S2: The sodium iron pyrophosphate precursor and the coating material are mixed to obtain a second mixture, and the second mixture is sintered a second time to obtain a sodium iron pyrophosphate cathode material with a coating layer. The coating material includes a second carbon source and a compound containing a triazine structure.
[0051] Traditional NFPP cathode materials typically undergo a single sintering process (i.e., a one-sintering process). During this process, the decomposition of raw materials such as sodium, iron, and phosphorus sources generates a large amount of volatile substances. If these substances are not removed in time, they will hinder the complete reaction and leave pores or impurities within the material. This can result in incomplete reactions, insufficient grain growth and perfect alignment, leading to problems such as poor crystallinity, numerous defects, and a high proportion of impurity phases in NFPP cathode materials. This application employs a two-sintering process (i.e., a two-sintering process). Through two sintering stages, the NFPP precursor is decomposed and recombined to form NFPP, effectively solving the problems of low NFPP purity and poor crystallinity caused by uneven raw material distribution, residual volatile components, and the presence of intermediate phases in the one-sintering process. This results in a purer and more stable NFPP phase. Specifically, in the first sintering process, raw materials such as sodium, iron, and phosphorus sources are mixed in stoichiometric proportions and heat-treated under an inert atmosphere (usually argon or nitrogen) to complete the initial solid-phase reaction, allowing the raw materials to decompose and undergo preliminary chemical combination, generating the rudimentary NFPP precursor of the target phase. A second sintering process is then performed to further eliminate the trace pores and volatile impurities remaining in the NFPP precursor from the first sintering, making the material denser and purer with a more complete crystal structure. This improves the phase purity and crystallinity of NFPP, which is beneficial to the electrochemical performance of NFPP.
[0052] During the formation of the NFPP crystalline phase, a coating layer is formed on the surface of the NFPP during the secondary sintering process. The triazine-containing compound in the coating material reacts in situ on the outer layer of the NFPP to form g-C3N4. Due to the unique two-dimensional layered structure of g-C3N4, this coating layer exhibits high conductivity, good stability, and fewer high-temperature side reactions, thus simply and efficiently improving the conductivity of the NFPP cathode material. Consequently, the NFPP cathode material possesses excellent cycle performance and rate capability. Furthermore, the optimal preparation temperature range of sodium iron pyrophosphate (NFPP) (the optimal temperature for secondary sintering, approximately 450℃-600℃) is basically consistent with the formation temperature of g-C3N4. When the raw material for preparing g-C3N4 (i.e., a compound containing a triazine structure) is added during mixing, g-C3N4 can be in situ coated onto the surface of sodium iron pyrophosphate. In contrast, ordinary carbon sources without triazine structures form carbon layers with low graphitization between 450℃ and 600℃. g-C3N4 can effectively improve the graphitization degree of the coating layer, thereby improving the conductivity and stability of the NFPP cathode material, which in turn improves the cycle performance and rate performance of the NFPP cathode material, and broadens the applicable temperature range of the NFPP cathode material.
[0053] Furthermore, compared to ordinary C3N4 coating, the g-C3N4 in the coating layer of this application exhibits superior performance. C3N4 refers to materials composed of C and N elements in a 3:4 molar ratio. It typically has an amorphous structure, and when used as a carbon and nitrogen source for coating, the improvement in electrical conductivity is primarily due to the doping effect of N. Compared to carbon, N has more free electrons and a lower band gap, resulting in better conductivity when doped C with N. However, g-C3N4 is a specific material with a defined structure. It is a layered material composed of carbon and nitrogen atomic layers stacked through van der Waals forces. It is a graphitic carbon nitride with a well-defined two-dimensional layered structure. Its structural strength, thermal stability, and electrical conductivity are all superior to C3N4, making it more conducive to forming a good coating layer. The improvement in material stability and conductivity is more significant, and the improvement in material performance is not achieved through N doping.
[0054] Furthermore, compared to preparing g-C3N4 pre-processed material and then adding it as a coating material, the g-C3N4 synthesized in situ in this application is more uniformly distributed in the coating layer, effectively providing a good conductive network, reducing the resistivity of the NFPP cathode material, and also allowing nitrogen elements in g-C3N4 to be uniformly introduced into the carbon layer, improving the electronic structure of g-C3N4 and further enhancing its intrinsic conductivity. This is because directly using g-C3N4 pre-processed material for coating is a physical mixing method, resulting in a coating layer that is mainly a discontinuous physical adhesion with weak bonding force and poor interface stability. It is also extremely prone to uneven coating, and agglomeration may even have a counterproductive effect. NFPP cathode materials are often used in applications involving high-rate charge and discharge, and a weak carbon layer is prone to detachment during cycling, thus losing its function. The in-situ reaction of compounds containing triazine structures to generate g-C3N4 is a kind of "in-situ construction". It is grown on the surface of NFPP through chemical reaction during the NFPP lattice growth process. It is more uniform and has certain chemical bonding effects. Compared with the weak van der Waals forces, it is stronger. This is beneficial to make the coating layer of NFPP cathode material more effective and long-lasting when the battery is discharged at high rate, and it greatly improves the cycle performance of NFPP cathode material.
[0055] Specifically, compounds containing a triazine structure can include at least one of urea, melamine, dicyandiamide, and thiourea. These materials have high C / N content and well-matched structures, making it easier to form the triazine ring, the constituent unit of g-C3N4, through secondary sintering. Urea is a more preferred compound, as it has a higher yield in forming g-C3N4, and its pyrolysis temperature is closer to the secondary sintering temperature.
[0056] During the secondary sintering process, the second carbon source in the coating material undergoes pyrolysis to generate amorphous carbon rich in defects. This carbon has a strong bonding force with the surface of NFPP particles and a high residual carbon rate, providing basic carbon coating and partial conductivity. Meanwhile, g-C3N4 is an inherently highly conductive sheet carbon that is uniformly distributed on the particle surface in situ. Due to its low residual carbon rate, it does not completely cover the particle surface. However, g-C3N4 can connect the disordered carbon (amorphous carbon) formed by the second carbon source to each other. Together, they form a coating layer, quickly establishing electronic pathways, constructing a conductive network, and enhancing the overall conductivity of the NFPP cathode material.
[0057] Therefore, the second carbon source in the coating material and the compound containing the triazine structure work together to form a more complete and continuous coating layer, which effectively improves the conductivity and stability of the NFPP cathode material, thereby giving the NFPP cathode material excellent cycle performance and rate performance.
[0058] In some embodiments, the second carbon source may include at least one of glucose, sucrose, starch, citric acid, and polyethylene glycol, with glucose being the preferred second carbon source. Sugars (starch, glucose, sucrose) have a high residual carbon rate during secondary sintering, and citric acid, representing severed-chain carbon, also has a similar effect to sugar carbon sources. Polymer long-chain carbon sources such as polyethylene glycol can encapsulate particles during liquid-phase milling, preventing sintering agglomeration and pyrolyzing to form a thin and uniform carbon layer, but their residual carbon rate is not as high as that of sugars or citric acid.
[0059] In some embodiments, the mass percentage of the coating material to the NFPP precursor can be 7% to 9%, which is beneficial for forming a coating layer of suitable thickness on the NFPP surface and for balancing the high capacity and high conductivity of the NFPP cathode material. This mass percentage can, exemplarily, be 7%, 7.5%, 8%, 8.5%, 9%, or any value within the range of any two of the above values. The mass ratio can further be 7.5% to 8.5%.
[0060] In the coating material, the mass ratio of the second carbon source to the compound containing the triazine structure can be (1.3~8):1. Within this mass ratio range, the coating layer can contain both an appropriate amount of g-C3N4 and an appropriate carbon content, which is beneficial to further improve the compounding effect of the second carbon source and the compound containing the triazine structure, and also beneficial to reduce the preparation cost.
[0061] In some embodiments, the mass percentage of the triazine-containing compound to the NFPP precursor can be 1% to 3%. This range effectively improves the conductivity of the NFPP cathode material while reducing the high-temperature cracking and gas production of the triazine-containing compound or its side reactions with the NFPP precursor, thereby improving the overall performance of the NFPP cathode material. Exemplarily, this mass percentage can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any value within the range of any two of the above values. The mass percentage can further be 1.5% to 2.5%, and even further, it can be 2%.
[0062] In some embodiments, the mass percentage of the second carbon source to the NFPP precursor can be 4% to 8%, which is beneficial for providing a suitable carbon content and improving the conductivity of the NFPP cathode material. This mass percentage can exemplary be 4%, 5%, 6%, 7%, 8%, or any value within the range of any two of the above values. The mass percentage can further be 5.5% to 6.5%.
[0063] In some embodiments, the secondary sintering temperature can be 450℃~600℃. A suitable secondary sintering temperature is beneficial for the formation of the NFPP phase and suppresses the formation of the impurity NFP phase, thereby improving the phase purity of the NFPP cathode material. Simultaneously, it allows compounds containing triazine structures to react in situ on the surface of the NFPP to form g-C3N4, and promotes a certain degree of graphitization of the second carbon source. The coating material forms a carbon coating layer containing g-C3N4, which is beneficial for further improving the conductivity of the NFPP cathode material. The secondary sintering temperature can, exemplarily, be 450℃, 500℃, 550℃, 600℃, or any value within the range of any two of the above values.
[0064] The holding time for the secondary sintering is 5h to 10h, which is beneficial for generating NFPP with a stable crystal structure and a stable coating layer. The holding time for the secondary sintering can be, for example, 5h, 6h, 7h, 8h, 9h, 10h, or any value within the range of any two of the above values.
[0065] In some embodiments, the heating rate for secondary sintering can be 2°C / min to 5°C / min. Slow heating facilitates the full in-situ reaction of compounds containing triazine structures to form g-C3N4, reducing localized overheating or uneven reaction during the secondary sintering process. It also promotes the formation of NFPP cathode materials with uniform particle size and stable structure. The heating rate for secondary sintering can, exemplarily, be 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, 5°C / min, or any value within the range of any two of the above values.
[0066] In some embodiments, step S2 may further include grinding the second mixture to obtain a second slurry, which is beneficial for further improving the uniformity of the mixture and controlling the particle size in the second slurry within a suitable range. Specifically, this may involve adding a solvent (e.g., at least one of water and ethanol) to the second mixture for grinding, which is beneficial for improving grinding efficiency.
[0067] In some embodiments, the median particle size D50 of the second slurry is 0.2 μm to 0.6 μm, which is beneficial for controlling the particle size of the NFPP cathode material obtained from the secondary sintering. The median particle size D50 of the second slurry can be, for example, 0.20 μm, 0.3 μm, 0.40 μm, 0.5 μm, 0.6 μm, or any value within the range of any two of the above values.
[0068] In some embodiments, the diameter of the grinding beads used in step S2 can be 0.3 mm to 0.6 mm.
[0069] Furthermore, before the first sintering, step S2 may also include spray drying the second slurry. Spray drying is beneficial for obtaining a dry second spray material with relatively uniform particle size and good flowability, which can improve the uniformity of the second sintering.
[0070] In some embodiments, the inlet air temperature of the spray drying in step S2 can be 180°C to 240°C, preferably 230°C, and the outlet air temperature can be 85°C to 110°C, preferably 90°C, which is beneficial for fully removing solvents and other volatile impurities in the second slurry.
[0071] In some embodiments, the carbon content of the NFPP cathode material can be 1.7% to 2.0%, which is beneficial for further improving the conductivity and rate performance of the NFPP cathode material while also taking into account its high capacity. The carbon content of the NFPP cathode material can, for example, be 1.7%, 1.75%, 1.8%, 1.85%, 1.9%, 1.95%, 2.0%, or any value within the range of any two of the above values.
[0072] Compared with existing technologies, the preparation method of sodium iron pyrophosphate cathode material of this application has the following advantages: 1. The coating material includes a second carbon source and a compound containing a triazine structure, which can achieve in-situ coating of g-C3N4 on the surface of NFPP and form a relatively complete and continuous coating layer. This can effectively improve the graphitization degree, conductivity and stability of the coating layer, provide a good conductive network, reduce the resistivity of NFPP cathode material, effectively improve the cycle performance and rate performance of NFPP cathode material, and broaden the applicable temperature range of NFPP cathode material.
[0073] 2. By controlling the temperature and time of secondary sintering, since the optimal preparation temperature range of NFPP is close to that of g-C3N4, the phase purity of NFPP and the graphitization degree and stability of the coating layer on the surface of NFPP are improved, which is beneficial to improving the conductivity and capacity of NFPP cathode material.
[0074] 3. This preparation method is simple and can improve the above-mentioned properties of NFPP cathode materials without increasing the process flow.
[0075] This application embodiment also provides a sodium iron pyrophosphate cathode material, which is prepared by the aforementioned method for preparing sodium iron pyrophosphate cathode material. The sodium iron pyrophosphate cathode material includes a sodium iron pyrophosphate matrix and a coating layer located on the outer layer of the sodium iron pyrophosphate matrix, wherein the coating layer contains g-C3N4.
[0076] Compared to existing technologies, the NFPP cathode material prepared by the aforementioned method provided in this application has NFPP with higher phase purity, and the coating layer on the surface of the NFPP contains g-C3N4. High-purity NFPP can improve the cycle stability and capacity of the NFPP cathode material; g-C3N4 has a unique two-dimensional layered structure, good stability, and high conductivity, which can effectively improve the conductivity and stability of the coating layer and reduce the resistivity of the NFPP cathode material. Therefore, the NFPP cathode material possesses excellent capacity, cycle performance, and rate performance.
[0077] This application also provides an electrochemical device (e.g., a secondary battery) that includes a positive electrode plate, the positive electrode plate including a positive electrode material, wherein the positive electrode material is the aforementioned sodium iron pyrophosphate positive electrode material.
[0078] Compared to existing technologies, the electrochemical device provided in this application embodiment has higher capacity and cycle performance during charging and discharging because it uses the aforementioned sodium iron pyrophosphate cathode material.
[0079] The present application's solution will be explained below with reference to embodiments. Those skilled in the art will understand that the following examples are for illustrative purposes only and should not be construed as limiting the scope of the application. Unless otherwise stated, reagents, software, and instruments involved in the following embodiments that are not specifically described are all conventional commercially available products or publicly disclosed.
[0080] Example 1 Step S1: Disperse 7.13 kg of sodium carbonate, 1.6 kg of glucose (first carbon source), and 135 g of titanium dioxide in 78 kg of water, then slowly add 4.81 kg of sodium dihydrogen phosphate. Sodium dihydrogen phosphate reacts with sodium carbonate to produce gas. Continue stirring for 30 min. After the reaction is complete, add 20 kg of ferric phosphate to obtain the first mixture. The main element ratio is Na:Fe:P = 4:3:4. The Ti element doping amount accounts for 0.3% of the theoretically calculated mass of NFPP, and the amount of glucose (first carbon source) added accounts for 8% of the mass of ferric phosphate.
[0081] The first mixture is ground to obtain a first slurry, wherein the grinding includes grinding in a sand mill (zirconium bead diameter 0.6 mm) until the median particle size D50 of the first slurry is about 1.0 μm.
[0082] Then, the first slurry is spray-dried to obtain a dry first spray material with relatively uniform particle size and good flowability. The inlet air temperature of the spray dryer is 230℃ and the outlet air temperature is 90℃.
[0083] The first spray material was then sintered once under an inert gas atmosphere, heated to 400°C at a heating rate of 3.5°C / min, held at that temperature for 7 hours, and finally cooled down to obtain an NFPP precursor with a carbon content of approximately 0.6%.
[0084] Step S2: Mix 16 kg of NFPP precursor, 0.96 kg of glucose (second carbon source) and 0.32 kg of urea (a compound containing a triazine structure) to obtain a second mixture, wherein the amount of glucose (second carbon source) added is 6.0% of the mass of NFPP precursor, and the amount of urea added is 2.0% of the mass of NFPP precursor. The second mixture is added to 17.28 kg of water, dispersed evenly, and ground to obtain a second slurry. The grinding includes grinding in a sand mill (zirconium bead diameter 0.3 mm) until the median particle size D50 of the second slurry is about 0.5 μm.
[0085] Then, the second slurry is spray-dried to obtain a dry second spray material with relatively uniform particle size and good flowability. The inlet air temperature for spray drying is 230℃ and the outlet air temperature is 90℃.
[0086] The pulverized material was sintered twice under an inert gas atmosphere, heated to 530℃ at a heating rate of 2.5℃ / min, held at that temperature for 7.5h, and finally cooled down to obtain an NFPP cathode material with a carbon content of about 1.8%.
[0087] Example 2: The difference from Example 1 is that in step S2, the amount of glucose added is 6.5% (i.e., 1.04 kg) of the NFPP precursor mass, and the amount of urea added is 1.0% (i.e., 0.16 kg) of the NFPP precursor mass. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0088] Example 3: The difference from Example 1 is that in step S2, the amount of glucose added is 5.5% (i.e., 0.88 kg) of the NFPP precursor mass, and the amount of urea added is 3.0% (i.e., 0.48 kg) of the NFPP precursor mass. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0089] Example 4: The difference from Example 1 is that the compound containing the triazine structure in step S2 is melamine. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0090] Example 5: The difference from Example 1 is that the compound containing the triazine structure in step S2 is dicyandiamide. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0091] Example 6: The difference from Example 1 is that the compound containing the triazine structure in step S2 is thiourea. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0092] Example 7: The difference from Example 1 is that in step S2, the second carbon source is citric acid, and the amount of citric acid added is 9.5% (i.e., 1.52 kg) of the NFPP precursor mass, while the amount of urea added is 2.0% (i.e., 0.32 kg) of the NFPP precursor mass. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0093] Comparative Example 1: The difference from Example 1 is that in step S2, the amount of glucose added is 7% of the mass of the NFPP precursor (i.e., 1.12 kg), and urea (i.e., a compound containing a triazine structure) is not added. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 1.
[0094] Comparative Example 2: The difference from Example 7 is that in step S2, the amount of citric acid added is 12% of the mass of the NFPP precursor (i.e., 1.92 kg), and urea (i.e., a compound containing a triazine structure) is not added. The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 7.
[0095] Comparative Example 3: Step S1: Disperse 7.13 kg sodium carbonate, 3 kg glucose, 0.54 kg urea, and 135 g titanium dioxide in 82.8 kg of water. Slowly add 4.81 kg sodium dihydrogen phosphate. The sodium dihydrogen phosphate reacts with the sodium carbonate to produce gas. Continue stirring for 30 minutes. After the reaction is complete, add 20 kg ferric phosphate to obtain a mixture. The main element ratio is Na:Fe:P = 4:3:4. The Ti element doping amount accounts for 0.3% of the theoretically calculated mass of NFPP, and the glucose addition amount accounts for 15% of the ferric phosphate mass. Grind the mixture to obtain a slurry. The grinding includes grinding in a sand mill (zirconium bead diameter 0.3 mm) until the median particle size D50 of the slurry is approximately 0.5 μm. Then, spray dry the slurry to obtain a dry, uniformly sized spray material with good flowability. The inlet air temperature for spray drying is 230℃, and the outlet air temperature is 90℃. The sprayed material was then sintered again under an inert gas atmosphere, heated to 500°C at a heating rate of 3.5°C / min, held at that temperature for 6 hours, and finally cooled down to obtain an NFPP cathode material with a carbon content of approximately 1.8%.
[0096] Comparative Example 4: The difference from Example 1 is that in step S2, the pre-prepared g-C3N4 product is used instead of urea. The amount of g-C3N4 added is 0.3% of the mass of the NFPP precursor (i.e., 0.048 kg; the carbon content provided by 0.048 kg of g-C3N4 is close to that provided by 0.32 kg of urea, ensuring that the carbon content of the final prepared NFPP cathode material is the same). The preparation methods of the remaining sodium iron pyrophosphate cathode material are basically the same as in Example 1. The g-C3N4 product is prepared by heating urea to 530°C at a heating rate of 2.5°C / min, sintering and holding at that temperature for 7.5 h, and finally cooling down.
[0097] Comparative Example 5: The difference from Example 7 is that in step S2, the pre-prepared g-C3N4 product is used instead of urea. The amount of g-C3N4 added is 0.3% of the mass of the NFPP precursor (i.e., 0.048 kg; the carbon content provided by 0.048 kg of g-C3N4 is close to that provided by 0.32 kg of urea, ensuring that the carbon content of the final prepared NFPP cathode material is the same). The preparation method of the remaining sodium iron pyrophosphate cathode material is basically the same as that in Example 7.
[0098] The following tests were performed on the sodium iron pyrophosphate cathode materials obtained in Examples 1-7 and Comparative Examples 1-5.
[0099] 1. Carbon content: The carbon content of the material is tested by infrared analysis. A carbon-sulfur analyzer is used. The sample is burned in a high-temperature and oxygen-rich state. The carbon element is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is quantitatively calculated by statistically analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.
[0100] 2. Powder compaction density: The test was conducted in accordance with the method specified in the standard "Determination of compaction density of lithium-ion battery cathode material powder" drafted by the National Technical Committee for Standardization of Nonferrous Metals.
[0101] 3. Powder resistivity: The test was conducted according to the method specified in the standard "Determination of Powder Resistivity of Cathode Material for Lithium-ion Batteries" drafted by the National Technical Committee for Standardization of Nonferrous Metals.
[0102] 4. Particle size test: The particle size distribution Dv50 was tested using a Malvern 3000 particle size analyzer after internal ultrasonic dispersion for 5 minutes.
[0103] 5. Scanning electron microscopy (SEM) test: A Zeiss Sigma 360 scanning electron microscope was used. This instrument has high-resolution imaging capabilities, which can clearly observe the microscopic morphology and structural features of materials, with a magnification of 10,000 times.
[0104] 6. X-ray diffraction (XRD) analysis: The test step size is 0.02°, the scanning speed is 2° / min, and the scanning angle is 5~60°.
[0105] 7. Electrochemical performance testing: Preparation of positive electrode sheet: (1) First, the prepared NFPP positive electrode material is sieved through a 200-mesh sieve. The material on the sieve is vacuum dried at 120°C for 12 hours before the positive electrode slurry is prepared. The NFPP positive electrode material accounts for 90% of the mass. Acetylene black is used as a conductive agent, and the mass of acetylene black accounts for 5%. Polyvinylidene fluoride (PVDF) is used as a binder, and the mass of PVDF accounts for 5%. The three are added together in N-methylpyrrolidone solvent according to the ratio, and ball milled to homogenize the slurry to obtain the positive electrode slurry. (2) The positive electrode slurry is evenly coated on the aluminum foil current collector, dried at 100°C, and then cut to obtain a positive electrode sheet of appropriate size. The mass of the active material NFPP is weighed and calculated in order to calculate the specific capacity.
[0106] Battery fabrication: A sodium sheet is used as the negative electrode, a polypropylene microporous membrane is used as the separator, and 1 mol / L sodium perchlorate (NaClO4) and a mixed carbonate-based organic solvent (ethylene carbonate / diethyl carbonate / fluoroethylene carbonate) are used as the electrolyte. The battery is assembled into a button cell in a glove box together with a gasket, spring sheet and positive and negative electrode shells.
[0107] The testing steps for coin cell performance include: (1) Charge / discharge capacity and first efficiency: The test was conducted on a LAND or Newway test system. At room temperature of 25°C, the battery was charged at a constant current of 0.1C (nominal specific capacity of 110mAh / g) to 3.65V, and then charged at a constant voltage until the current dropped to 0.05C. The charging was stopped, and the first charge specific capacity was recorded. Then it was discharged at 0.1C to the cutoff voltage of 2.0V, and the first discharge specific capacity was recorded. The first charge / discharge efficiency of the battery was calculated according to the following formula, i.e., the first efficiency: First charge / discharge efficiency = (first discharge specific capacity / first charge specific capacity) ×100%.
[0108] (2) Cyclic performance: The test was conducted on the LAND or Xinwei test system. At room temperature of 45℃, the battery was charged at a constant current of 1C (nominal specific capacity of 110mAh / g) to 3.6V, and then charged at a constant voltage until the current dropped to 0.05C. The charging was stopped and the charging specific capacity was recorded. Then it was discharged at 1C to the cutoff voltage of 2.0V and the first discharge specific capacity was recorded. After resting for 5 minutes, the next charge and discharge cycle was started. The cycle capacity retention rate = (discharge specific capacity at the 100th cycle / discharge specific capacity at the 1st cycle) × 100%.
[0109] (3) Rate performance: The test was conducted on the LAND or Xinwei test system. At room temperature of 25°C, the battery was charged at a constant current of 5C (nominal specific capacity of 110mAh / g) to 3.65V, and then charged at a constant voltage until the current dropped to 0.05C. The charging was stopped and the charging specific capacity was recorded. Then the battery was discharged at 5C to the cutoff voltage of 2.0V and the first discharge specific capacity was recorded.
[0110] The test results of Examples 1-7 and Comparative Examples 1-5 are as follows: Figures 3 to 12 And as shown in Table 1.
[0111] Table 1 The above results indicate that: From Table 1 and Figures 8 to 12 It can be seen that, compared with Comparative Examples 1, 3, and 4, the NFPP cathode material prepared in Example 1 is superior in terms of compaction density, resistivity, and coin cell performance. The resistivity in Example 1 is only 1.3 × 10⁻⁶. 4 The resistivity in Comparative Examples 1, 3, and 4 is as high as 6.8 × 10⁻⁶. 5 above.
[0112] Combination Figure 3 and Figure 4 The comparison shows that the coating material in Example 1 contains urea, which, after secondary sintering, forms g-C3N4 with a two-dimensional layered structure in situ on the surface of NFPP. Figure 3 The presence of lamellar carbon on the surface of the material indicates successful in-situ coating of g-C3N4, while Comparative Example 1 only shows an NFPP cathode material prepared using glucose as the coating material. Figure 4 No carbon lamellae appeared on the surface of the material in Example 1. Therefore, the conductivity of Example 1 is better than that of Comparative Example 1. Resistivity mainly affects electron transport during the charging and discharging process, and the difference will be more obvious when discharging at high rates. The point-counting performance of Example 1 is also better than that of Comparative Example 1.
[0113] Comparing Example 1 and Comparative Example 3, the results show that the two-calcination process (i.e., the preparation method in Example 1) using glucose as a carbon source and in-situ coating with g-C3N4 is more advantageous than the one-calcination process (i.e., the preparation method in Comparative Example 3), especially in terms of resistivity and coin cell performance. Figure 8 It can be clearly seen that Comparative Example 3 has a significant peak around 34.3°, which is one of the main peaks of the heterogeneous sodium iron phosphate. This indicates that the one-time calcination process is not conducive to high phase purity. In Example 1, NFPP has higher phase purity, which is beneficial to improving capacity performance.
[0114] Comparing Example 1 with Comparative Example 4, the results show that in Example 1, the in-situ formation of g-C3N4, compared to Comparative Example 1 where g-C3N4 was first prepared and then added as a coating material, resulted in a more uniform distribution of g-C3N4 in the coating layer. This effectively provides a good conductive network, reduces the resistivity of the NFPP cathode material, and the coating layer in Example 1 is also more effective and durable, significantly improving the cycle performance of the NFPP cathode material.
[0115] In Examples 1-3, the mass percentage of the coating material to the NFPP precursor is in the range of 5% to 11%, which is beneficial to forming a coating layer of suitable thickness on the NFPP surface. Adjusting the mass percentage of the triazine-containing compound in the coating material to the NFPP precursor to 1% to 3% is beneficial to further improve the conductivity of the NFPP cathode material. The preferred mass percentage of the triazine-containing compound to the NFPP precursor is 2%.
[0116] Combination Figure 3 and Figure 5 And in Table 1, among Examples 1 and 7, the performance of Example 1 is better than that of Example 7. This is because glucose is more effective as a second carbon source than citric acid. This is mainly because the surface coating of NFPP particles is denser when citric acid is used, while the surface coating of NFPP particles is looser when glucose is used, which is more conducive to electron transport and further reduces resistance.
[0117] It is understood that the above embodiments are merely exemplary implementations used to illustrate the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a sodium iron pyrophosphate cathode material, characterized in that, include: Sodium source, iron source, phosphorus source and first carbon source are mixed to obtain first mixture, and the first mixture is sintered once to obtain sodium iron pyrophosphate precursor; as well as The sodium iron pyrophosphate precursor and the coating material are mixed to obtain a second mixture, and the second mixture is sintered twice to obtain the sodium iron pyrophosphate cathode material with a coating layer. The coating material includes a second carbon source and at least one of urea, melamine, dicyandiamide and thiourea. The temperature of the secondary sintering is 450℃~600℃, and the holding time of the secondary sintering is 5h~10h.
2. The preparation method according to claim 1, characterized in that, The mass percentage of the coating material to the sodium iron pyrophosphate precursor is 7% to 9%.
3. The preparation method according to claim 2, characterized in that, In the coating material, the mass ratio of the second carbon source to at least one of the urea, melamine, dicyandiamide and thiourea is (1.3~8):
1.
4. The preparation method according to claim 2, characterized in that, The mass percentage of at least one of urea, melamine, dicyandiamide, and thiourea to the sodium iron pyrophosphate precursor is 1% to 3%; and / or The second carbon source has a mass percentage of 4% to 8% of the sodium iron pyrophosphate precursor.
5. The preparation method according to claim 1, characterized in that, The second carbon source includes at least one of glucose, sucrose, starch, citric acid, and polyethylene glycol.
6. The preparation method according to claim 5, characterized in that, The second carbon source is glucose.
7. A sodium iron pyrophosphate cathode material, characterized in that, The sodium iron pyrophosphate cathode material is prepared by the method for preparing sodium iron pyrophosphate cathode material as described in any one of claims 1 to 6. The sodium iron pyrophosphate cathode material includes a sodium iron pyrophosphate matrix and a coating layer located on the outer layer of the sodium iron pyrophosphate matrix, wherein the coating layer contains g-C3N4.
8. An electrochemical device, characterized in that, The electrochemical device includes a positive electrode plate, the positive electrode plate includes a positive electrode material, and the positive electrode material is the sodium iron pyrophosphate positive electrode material as described in claim 7.
Citation Information
Patent Citations
Modified lithium manganese iron phosphate material as well as preparation method and application thereof
CN118888729A
Molybdenum carbide / nitrogen-doped carbon composite material and preparation method and application thereof
CN119542389A
